The identification of problems related to electronic financial statements – own research results - Judkowiak, Agnieszka (Identyfikacja problemów związanych z elektronicznymi sprawozdaniami finansowymi – wyniki badań własnych, 2019)
E-financial statements constitute a new dimension of financial reporting in Poland. They were introduced in response to the ongoing digitization of the economy. These changes resulted in a number of problems for the accountants, which the legislator did not foresee. The purpose of the work was to identify problems arising during the preparation, signing and submission of e-financial statements. The research material was collected using the direct survey method. The research tool was a survey questionnaire. The respondents were people who prepared at least one e-financial statement for 2018. The conducted research shows that most of the identified problems are the consequence of the too rapid introduction of the new regulations without introducing a transitional period for the whole of the new requirements
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 6, s. 40-50
Keywords: financial reporting; e-financial statements; Accounting Act; electronic signature; ePUAP; sprawozdawczość finansowa; e-sprawozdanie finansowe; ustawa o rachunkowości; podpis elektroniczny